2019
DOI: 10.1002/ajcp.12350
|View full text |Cite
|
Sign up to set email alerts
|

Liberating and Empowering Effects of Critical Reflection on Collective Action in LGBT and Cisgender Heterosexual Individuals

Abstract: Critical consciousness represents the transformation from a passive target of oppression to an active actor with an increased capacity to analyze and negotiate conditions of oppression. It is considered as an antidote for oppression that can liberate people from oppressive ideologies and empower them to resist social injustice. Building on the theory of critical consciousness and the Social Identity Model of Collective Action, this paper examined the liberating and empowering effects of critical reflection on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Previous studies have shown the positive association of critical consciousness with self‐esteem among LGB individuals (Chan & Mak, 2020; Velez & Moradi, 2016). The unique contribution of our study, however, lies in our discovery that the association was partially mediated, and could be partly explained, by identity affirmation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies have shown the positive association of critical consciousness with self‐esteem among LGB individuals (Chan & Mak, 2020; Velez & Moradi, 2016). The unique contribution of our study, however, lies in our discovery that the association was partially mediated, and could be partly explained, by identity affirmation.…”
Section: Discussionmentioning
confidence: 90%
“…They may also gain a greater sense of agency and mastery and develop higher levels of identity pride (i.e., feeling dignified as a result of one’s own sexual identity) and identity superiority (i.e., viewing one’s own sexual identity more favorably than other sexual identities; Becker et al., 2011; Thomas & Louis, 2013). The potential psychological outcomes are higher levels of self‐acceptance, self‐affirmation, and self‐respect and lower levels of self‐stigma, self‐blame, and self‐shame (Chan & Mak, 2020; Velez & Moradi, 2016; Watts et al., 2011; Watts & Hipolito‐Delgado, 2015).…”
Section: Critical Consciousness and Sense Of Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…CC has also been identified as a protective factor for marginalized groups (Chan & Mak, 2019; Diemer, Rapa, Voight, & McWhirter, 2016; Puckett, Zachary DuBois, McNeill, & Hanson, 2019). Chan and Mak (2019), for example, examined the liberating effects of CC development on collective action for minority rights.…”
Section: Fundamental Components Of CCmentioning
confidence: 99%
“…The field of community psychology has long advocated for research and action focused on the rights and well-being of sexual and gender minorities (SGMs;D'Augelli, 1989;Garnets & D'Augelli, 1994;Harper & Schneider, 2003). In line with this aim, literature is emerging in the field focused on SGM resilience (e.g., Kosciw, Palmer, & Kull, 2015), intersectionality and intersections with other aspects of culture and identity (e.g., Beasley, Jenkins, & Valenti, 2015;Harper & Wilson, 2017), interventions to decrease prejudice and enhance health and well-being (e.g., Nieves-Lugo, Rohrbeck, Nakamura, & Zea, 2017), and the positive impact of activism and collective action to support SGMs and SGM rights (Chan & Mark, 2019;Frost, Fine, Torre, & Cabana, 2019). Research in the field also has focused on heterosexism (e.g., Chesir-Teran, 2003;D'Augelli, 2003;Hoy-Ellis & Fredriksen-Goldsen, 2017) and masculinity ideologies (e.g., Wilson et al, 2010) that reinforce SGM oppression and contribute to decreased well-being.…”
Section: Introductionmentioning
confidence: 99%